(untitled) (Research, Society and Development, 2024)
Introduction: The early onset of cigarette consumption represents a serious public health issue, exacerbated by the highly addictive nature of tobacco and its harmful effects, which increase the risk of early death. The introduction of electronic cigarettes, initially considered an alternative to tobacco, has worsened the situation, especially among young people, due to the appeal of attractive models and flavored aromas. These devices have contributed to increased nicotine addiction and the potential transition to conventional smoking. Objective: To promote discussion on the need for stricter regulations and prevention strategies to protect young people from the risks associated with the use of tobacco products and electronic cigarettes. Method: A literature review was conducted using PUBMED (National Library of Medicine) to search for articles with the descriptors “electronic cigarette” AND “teenagers” and “electronic cigarette” AND “students.” Results: After the initial screening of 61 articles, 28 articles not aligned with the study’s objectives were excluded, resulting in 33 articles. After the initial screening of 61 articles, 28 that did not align with the study objectives were eliminated, resulting in 33 articles. In the filtering process, we ended up with 23 final articles. Conclusion: Electronic cigarettes have proven to be as harmful as, or even more harmful than, conventional cigarettes, posing significant health risks. It is essential to implement stricter regulations, such as banning their use in public places and promoting educational campaigns. Additionally, future studies should explore adolescent behavior and perceptions regarding electronic cigarettes to improve prevention strategies.